A Gq Biased Small Molecule Active at the TSH Receptor - Latif, Rauf; Morshed, Syed A.; Ma, Risheng; Tokat, Bengu; Mezei, Mihaly; Davies, Terry F. (Frontiers in Endocrinology, 2020)
G protein coupled receptors (GPCRs) can lead to G protein and non-G protein initiated signals. The TSH receptor (TSHR) has a unique ability to engage different G proteins making it highly amenable to selective signaling. In this study, we describe the identification and characterization of a novel small molecule agonist to the TSHR which induces primary engagement with Gq/11. To identify allosteric modulators inducing selective signaling of the TSHR we used a transcriptional-based luciferase assay system with CHO-TSHR cells stably expressing response elements (CRE, NFAT, SRF or SRE) that were capable of measuring signals emanating from the coupling of Gαs, Gαq/11, Gβγ, and Gα12/13 respectively. Using this system, TSH activated Gαs, Gαq/11 and Gα12/13 but not Gβγ. On screening a library of 50K molecules at 0.1,1.0 and 10μM, we identified a novel Gq/11 agonist (named MSq1) which activated Gq/11 mediated NFAT-luciferase greater than 4 fold above baseline and had an EC50= 8.3 x 10-9 M with only minor induction of Gαs and cAMP. Furthermore, MSq1 is chemically and structurally distinct from any of our previously reported TSHR agonist molecules. Docking studies using a TSHR transmembrane domain (TMD) model indicated that MSq1 had contact points on helices H1, H2, H3 and H7 in the hydrophobic pocket of the TMD and also with the extracellular loops. On co-treatment with TSH, MSq1 suppressed TSH-induced proliferation of thyrocytes in a dose-dependent manner but lacked the intrinsic ability to influence basal thyrocyte proliferation. This unexpected inhibitory property of MSq1 could be blocked in the presence of a PKC inhibitor resulting in derepressing TSH induced protein kinase A (PKA) signals and resulting in the induction of proliferation. Thus the inhibitory effect of MSq1 on proliferation resided in its capacity to overtly activate protein kinase C (PKC) which in turn suppressed the proliferative signal induced by activation of the predomiant cAMP-PKA pathway of the TSHR. In summary, we identified and characterized a novel Gαq/11 agonist molecule acting at the TSHR and which showed a marked anti-proliferative ability. Hence, Gq biased activation of the TSHR may offer a therapeutic option for thyroid growth modulation.